PENGARUH PEMASARAN DAN KUALITAS PELAYANAN KOPERASI TERHADAP LOYALITAS NASABAH DENGAN KEPERCAYAAN PELANGGAN SEBAGAI VARIABEL INTERVENING DI KOPERASI ARTHA AGUNG BANDAR: Dibuat Oleh Tri Yulinda Riskawati, Sobrotul Imtikhanah, R. Irawan Supriyatno - irawan supriyatno; sobrotul imtikhanah; tri yulinda (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
Customer loyalty has a very important role in a company. Loyalty is the result of establishing both short-term and long-term relationships with customers. Trust is important for companies to build relationships with customers because customers cannot build real relationships without trust. This study aims to determine the effect of marketing and service quality of cooperatives on customer loyalty with customer trust as an intervening variable in the Koperasi Artha Agung Bandar. The sampling technique used purposive sampling, as many as 90 respondents. This study uses a quantitative description method. For data collection using questionnaire. T-test results show that marketing has a significant positive effect on customer loyalty and service quality has an insignificant negative effect on customer loyalty. Marketing has an insignificant negative effect on customer trust and service quality has a significant positive effect on customer trust. By using path analysis, customer trust is able to mediate for service quality to customer loyalty, but customer trust is not able to mediate for marketing to customer loyalty. From the results of the research conducted, it is concluded that marketing has no positive and significant effect on customer loyalty with customer trust as an intervening variable in the Koperasi Artha Agung Bandar, while the service quality of cooperatives has a positive and significant effect on customer loyalty with customer trust as an intervening variable in the Koperasi Artha Agung Bandar.